PRIMER REPORTE DE NEFROPATÍA JUVENIL (DISPLASIA RENAL) EN UNA GOLDEN RETRIEVER - Tabacchi N., Luis (2004)
Juvenile nepropathy was diagnosed in a female Golden Retriever of three months of age, with clinical signs compatible with chronic renal failure. The diagnosis was based on the presence of persistent poorly differentiated renal tissue (immature glomeruli and tubules, and persistent mesenchyme) on histopathological examination.